Current situation, problems and solution proposals of cold storages in Karaman province - Nizam Mustafa NİZAMLIOĞLU; Süleyman GÖKMEN (Derim, 2017)
In this study, the current situation and problems of cold storage in Karaman province was investigated. The data were obtained by means of survey study. For this purpose, the business owners of 37 cold storage facilities were interviewed face to face. In the present cold storages, it has been found that there are important problems. The most important problems are the high power consumption, the lack of a stock market to determine the prices for especially apples, the lack of modernization in cold storages and the significant problems in export. If these problems are resolved, both public and country economy will gain.